Mental toughness in sport. Systematic review and future - Liew, G. C.; Kuan, G.; Chin, N. S.; Hashim, H. A. (German Journal of Exercise and Sport Research, 2019)
Mental toughness refers to a collection of psychological characteristic which are central to optimal performance. Athletes, coaches, and sport psychologists have consistently implicated mental toughness as one of the most important psychological characteristics related to success in sports. Over the last few decades, numerous studies have been conducted to examine the role of mental toughness in sporting success. However, its conceptualization and measurement are without consensus. The purpose of this study is to systematically review some of the emerging definitions and conceptualizations, and examine how mental toughness could be nurtured. This review considers both qualitative and quantitative approaches to the study of mental toughness with the specific focus on the models and the development of the measurement of this construct. Although these discussions center on the general aspects of mental toughness, we believe many of the issues have relevance to scholars and practitioners who are interested in the measurement of psychological variables as they pertain to sport, exercise, and other performance or achievement contexts. Mentale Stärke zählt zu einer Reihe psychologischer Fähigkeiten, die wichtig für optimale Leistung sind. Durchgängig verweisen Sportler, Trainer und Sportpsychologen auf mentale Stärke als eine der wichtigsten psychologischen Fähigkeiten für den Erfolg im Sport. Deshalb wurden über die letzten Jahrzehnte viele Untersuchungen zur Bedeutung von mentaler Stärke für den sportlichen Erfolg durchgeführt. Es besteht jedoch kein Konsens bezüglich der Konzeptualisierung und Erfassung dieser Fähigkeit. Ziel der vorliegenden Studie ist es, einen systematischen Überblick über Definitionen und Konzeptualisierungen zu geben und zu betrachten, wie mentale Stärke verbessert werden kann. Die Übersicht berücksichtigt qualitative und quantitative Ansätze zur Untersuchung von mentaler Stärke mit einem speziellen Fokus auf Modellen und der Entwicklung von Messinstrumenten für dieses Konstrukt. Zwar konzentriert sich diese Betrachtung auf allgemeine Aspekte von mentaler Stärke, wir glauben aber, dass viele dieser Fragen relevant für Wissenschaftler und Praktiker sind, die an der Erfassung von psychologischen Variablen interessiert sind, da sie mit Sport, körperlicher Aktivität und anderen Kontexten der Leistungserbringung in Verbindung stehen.